Chemistry and analysis of radionuclides : laboratory techniques and methodology - Lehto, Jukka; Hou, Xiaolin (Weinheim : Wiley-VCH, 2010)
Written by chemists for chemists, this is a comprehensive guide to the important radionuclides as well as techniques for their separation and analysis. It introduces readers to the important laboratory techniques and methodologies in the field, providing practical instructions on how to handle nuclear waste and radioactivity in the environment.
Radionuclides and their Radiometric Measurement -- Special Features of the Chemistry of Radionuclides and their Separation -- Factors Affecting Chemical Forms of Radionuclides in Aqueous Solutions -- Separation Methods -- Yield Determinations and Counting Source Preparation -- Radiochemistry of the Alkali Metals -- Radiochemistry of the Alkaline Earth Metals -- Radiochemistry of the 3d-Transition Metals -- Radiochemistry of the 4d-Transition Metals -- Radiochemistry of the Lanthanides -- Radiochemistry of the Halogens -- Radiochemistry of the Noble Gases -- Radiochemistry of Tritium and Radiocarbon -- Radiochemistry of Lead, Polonium, Tin, and Selenium -- Radiochemistry of the Actinides -- Speciation Analysis -- Measurement of Radionuclides by Mass Spectrometry -- Sampling and Sample Pretreatment for the Determination of Radionuclides -- Chemical Changes Induced by Radioactive Decay.
Includes bibliographical references and index.
Print version record.
Keywords: Radioisotopes -- Analysis -- Laboratory manuals; Radioactive substances -- Analysis -- Laboratory manuals; Radioisotopes -- Analysis -- Laboratory manuals; Radioisotopes; Science; Physics; Engineering; Electrical engineering; SCIENCE -- Chemistry -- Physical & Theoretical; Radioactive substances -- Analysis; Radioisotopes -- Analysis; Electronic books; Laboratory manuals